Yunyye aktivisty Sovetskogo Krasnogo Kresta! Ukreplyayte internatsional'nuyu druzhbu! - Sebryuk, V. I (1982)
Flower blooming with smiling faces of European, Asian and Africa children rising above Original title: Юные активисты Советского Красного Креста! Укрепляйте интернациональную дружбу! PO-0768